ENDORSEMENTS (Tufts Archival Research Center, 2007)
Marginalia; Memo to Californians for Common Sense from Woodward & McDowell regarding endorsements. Discusses allegiance of the Sacremento Bee, the UAW, and the California Wild Life Federation.